Residential location and household spending: Exploring the relationship between neighborhood characteristics and transportation and housing costs - Schouten, Andrew (Urban Affairs Review)
Using data from the Panel Study of Income Dynamics and a seven-category neighborhood typology, this analysis examines the relationship between urban form and household spending. Results suggest that poor households living in urban areas have lower transportation expenditures than their counterparts in sprawling suburbs. Lower transportation costs, however, do not offset high housing prices, with poor households paying particularly high premiums for housing in the densest, most transit-rich neighborhoods. Households above the poverty threshold also benefit from reductions in transportation costs, especially in intensely urban areas. Nevertheless, these low transportation costs are not associated with lower overall expenditures; instead, they countervail high housing premiums, meaning that the most transit-rich neighborhoods do not offer cost savings relative to other neighborhood types. Findings highlight the need to expand the supply of both transit and housing in communities where poor households can leverage affordable transportation options to reduce their combined expenditure burden.- Reproduced
Keywords: Residential location, Location efficiency, Transpiration expenditures, Housing expenditures, Billet environment